Contemporary problems in studying population of Vojvodina Province - S. Djurdjev, Branislav; Arsenović, Daniela; Dragin, Aleksandra (Acta geographica Slovenica, 2010)
This paper identifies nine contemporary problems that hamper the population research in Vojvodina Province (northern part of Republic of Serbia) at the beginning of the twenty-first century. These problems are: postponement of census to 2002, changes of the definition of permanent population, different definitions in available data of current statistics, changes of the definition of the urban settlement term, changes in the total number of settlements, decreased number of available data of current statistics, absence of the bulletin of current statistics, absence of population register and absence of regional institution for population studies. That implies that collected data in the censuses are often not comparable due to slight changes in methodology, changes in state borders.